Financial ratio analysis (case study on pharmaceutical industry in indonesia listed on the indonesia stock exchange year 2012-2014 - Annisa Fatkhul Jannah ((JRAMB) Jurnal Riset Akuntansi Mercu Buana, 2016)
AbstrakThe purpose of this thesis is to analyze the financial performance of pharmacycompanies are included in the main board at the Indonesia Stock Exchange based on the results of the analysis of financial ratios on the financial statements of each company during the period 2012-2014.The method used is descriptive research by analyzing financial statements using quantitative data and data analysis techniques used by the researchers are financial ratios, namely Liquidity Ratios, SolvencyRatios, Activity Ratios and Profitability Ratios. The results based on the liquidity ratio current ratio PT Darya Varia Laboratoria current ratio have a value higher than the company's competitors. Acid test ratio PT Sido Appears Pharmaceutical Industry Tbk acid test ratio has a value higher than the company's competitors. Value solvency ratio debt ratio has a value of PT Indofarma Tbk highest debt ratio than the company's competitors. The value of the accounts receivable turnover ratio of activity of PT Darya Varia Laboratoria Tbk has the lowest value of the accounts receivable turnover compared to the company's competitors. The value of inventory turnover and Pharmaceutical PT Industri Jamu Sido Appears Tbk has the highest inventory turnover value than the company's competitors. Fixed asset turnover value of PT Kalbe Farma Tbk has the highest value of fixed asset turnover than the company's competitors. Toral turnover value of assets of PT Kalbe Farma Tbk has the highest value of total asset turnover than the company's competitors. Value gross profit margin profitability ratios PT Taisho Pharmaceutical Indonesia Tbk have the value